2017
DOI: 10.3390/polym9020036
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Biodegradable Polymer Properties on Antifouling Paints Activity

Abstract: Abstract:The development of new antifouling paints requires understanding the parameters involved in antifouling activity and to develop new analytical tools for their evaluation. A series of biodegradable poly(ε-caprolactone-co-δ-valerolactone) copolymers varying by molecular weight and composition were synthesized, characterized and formulated as antifouling paints. The physico-chemical properties such as hydration, degradation, erosion and lixiviation of paints were studied. Microfouling (bacteria and micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 56 publications
(98 reference statements)
0
14
0
Order By: Relevance
“…Only a few studies have focused on the use of CLSM to study biofilm development on antifouling paints [ 20 , 48 , 49 ]. CLSM make it possible to represent the 3D-architecture of the sample and to extract quantitative structural parameters such as the biofilm biovolume and thickness.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a few studies have focused on the use of CLSM to study biofilm development on antifouling paints [ 20 , 48 , 49 ]. CLSM make it possible to represent the 3D-architecture of the sample and to extract quantitative structural parameters such as the biofilm biovolume and thickness.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it is possible to compare the inhibition rate of microfouling. In Loriot et al [ 20 ], antifouling paints based on P(CL-VL) and commercial CDP was studied and compared to standard without biocide. The rate of inhibition was 95% on average for diatom biomass and maximum thickness after six weeks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of paint with Tween 80 as additive, a decrease of biomass and average thickness was observed after 7 weeks. This result can be explained by a mechanical erosion of paint surface, as already observed in the case of erodible paints [9,24].…”
Section: Resultsmentioning
confidence: 57%
“…For a long time, painting antifouling coatings on seawater-impregnated substrates has been an effective way to inhibit the attachment of marine organisms. It has been widely applied, such as in shipping vessels, heat exchangers, offshore rigs, jetties, aquaculture cages, and other submerged structures in the marine environment [6,7]. Meanwhile, one statistical analysis indicated that the practice saves the global shipping industry an estimated 150 billion US dollars per year [8].…”
Section: Introductionmentioning
confidence: 99%